2017
DOI: 10.1039/c7ce00118e
|View full text |Cite
|
Sign up to set email alerts
|

Computational screening of covalent organic frameworks for the capture of radioactive iodine and methyl iodide

Abstract: Large-scale computational screening results show that COFs are promising materials for the capture of radioactive iodic contaminants from nuclear wastes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…To date, a certain number of POPs have been employed for this purpose, such as nanoporous organic polymers (NOPs), 134 conjugated microporous polymers (CMPs) 139,141,142 such as metalloporphyrin-based CMPs 138 and hexaphenylbenzene-based CMPs, 135 azo-bridged porous triptycene networks 140,143 and crystalline covalent organic frameworks (COFs). [111][112][113][114]117,128 Chen et al 134 studied the iodine adsorption performance of a series of hierarchically porous organic polymers based on tetraphenyladamantane (named as NOP-53, NOP-54 and NOP-55). Their pore properties were controlled by adjusting the lengths and rigidities of the linkers; for example, rigid tetrahedral building blocks of 1,3,5,7-tetraphenyladamantane were linked with exible alkyl chains to obtain different hierarchical NOPs.…”
Section: Covalently Linked Porous Organic Polymers (Pops)mentioning
confidence: 99%
See 2 more Smart Citations
“…To date, a certain number of POPs have been employed for this purpose, such as nanoporous organic polymers (NOPs), 134 conjugated microporous polymers (CMPs) 139,141,142 such as metalloporphyrin-based CMPs 138 and hexaphenylbenzene-based CMPs, 135 azo-bridged porous triptycene networks 140,143 and crystalline covalent organic frameworks (COFs). [111][112][113][114]117,128 Chen et al 134 studied the iodine adsorption performance of a series of hierarchically porous organic polymers based on tetraphenyladamantane (named as NOP-53, NOP-54 and NOP-55). Their pore properties were controlled by adjusting the lengths and rigidities of the linkers; for example, rigid tetrahedral building blocks of 1,3,5,7-tetraphenyladamantane were linked with exible alkyl chains to obtain different hierarchical NOPs.…”
Section: Covalently Linked Porous Organic Polymers (Pops)mentioning
confidence: 99%
“…COFs have a well-ordered architecture with particularly interesting structural properties, such as a low structural density, easily tuned porosity, elevated specic surface areas, and quite high thermal (up to 600 C in the best case) and chemical stability, as well as a wide range of functionalization. 117,128,198 Lan et al 128 used computational studies to determine the theoretical adsorption capacities of COFs for iodine (I 2 ) and iodomethane (CH 3 I) in the conditions of real applications. The results show that 3D-COFs have the best adsorption performance for I 2 and CH 3 I in contrast to 2D-COFs.…”
Section: Covalently Linked Porous Organic Polymers (Pops)mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering various MOF materials with aluminum as a metal center, Loiseau et al showed that the sorption of I 2 in combination with liquid cyclohexane was the highest on samples containing a grafted NH 2 group when compared to pristine materials [ 54 ]. On the other hand, computational studies have also been performed to screen the performances of other selected MOFs [ 55 , 56 , 57 ]. Furthermore, some sorbents for radionuclide species have also been designed from UiO-66 and ZIFs series with enhanced retention performances [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the enrichment and toxic effects in organisms, effective methods for the capture and removal of radiological iodine aroused strong concerns. To date, several strategies have been proposed, including dry dedusting [5,6], chemical precipitation [7], and physical adsorption [8][9][10]. Among them, the physical adsorption method has specific advantages of high adsorption efficiency, low cost, simple operation, and high recyclability [11,12].…”
Section: Introductionmentioning
confidence: 99%